SISTEM INFORMASI MANAJEMEN SUPERCHARGER DENGAN KONTROL PROPORTIONAL INTEGRAL DERIVATIVE PADA MOTOR MATIC - Irawan, Ibnu; Fatah, Doni Abdul; Budiarto, Hairil (Universitas Trunojoyo Madura, 2024)
One of the main problems occurring on this earth is air pollution and the reduction in the amount of fuel oil. The main aim of the research is to regulate the mixture of fuel and air so that it burns ideally, so that the resulting emissions are non-toxic and environmentally friendly. This research is a technological development as a means of information and comparison before and after a supercharger is installed. Adjust the AFR (Air Fuel Ratio) value through the inlet air channel to obtain the ideal ratio of fuel and air so that the mixture becomes stoichiometric. The air intake is regulated into the engine by adding a supercharger using the Proportional Integral Derivative (PID) control method. The supercharger works by using a lambda sensor as data input for a poor or rich mixture, then the lambda sensor value is entered into the PID method. The PID value will determine the speed of the brushless motor which aims to obtain stoichiometric AFR. A lambda sensor that is close to the 0.5 setpoint is expected to produce a more ideal mixture of air and gasoline.Keywords: Management Information, Supercharger, Proportional Integral Derivative, Automatic Motorcycles.